2016
DOI: 10.1186/s12891-016-1180-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and its risk factors for low back pain among operation and maintenance personnel in wind farms

Abstract: BackgroundWith the increasingly severe energy shortage and climate change problems, developing wind power has become a key energy development strategy and an inevitable choice to protect the ecological environment worldwide. The purpose of this study was to investigate the prevalence of low back pain (LBP) and analyze its risk factors among operation and maintenance personnel in wind farms (OMPWF).MethodsA cross-sectional survey of 151 OMPWF was performed, and a comprehensive questionnaire, which was modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
1
11
0
1
Order By: Relevance
“…Sample sizes in studies that directly examined study subjects ranged from 10-603. Response rates were high in those cross-sectional studies that reported appropriate values (73-100%) (23,25,(28)(29)(30)(31)39). Proportions of female workers varied between 0-45.1%.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Sample sizes in studies that directly examined study subjects ranged from 10-603. Response rates were high in those cross-sectional studies that reported appropriate values (73-100%) (23,25,(28)(29)(30)(31)39). Proportions of female workers varied between 0-45.1%.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…According to a systematic review from 2014, no evidence was identified on the association between working on onshore wind turbines and the risk of musculoskeletal disorders (26). A later-published cross-sectional study observed a very high prevalence of low-back pain among operation and maintenance personnel working on onshore wind farms (39). A fatal incident that occurred during the loading process of a wind tower was reported (34) as was a polytrauma of an electrician after a fall from an onshore wind turbine (35).…”
Section: Summary Of the Body Of Evidencementioning
confidence: 99%
See 3 more Smart Citations